Total Synthesis of Mycocyclosin and the Herqulines - Ryan, Jonathon S.; Schindler, Corinna S. (Synthesis, 2021)
Since the first reports of their isolation, mycocyclosin and the herquline family of natural products have attracted interest from the synthetic community for their uniquely strained macrocyclic architectures. This review describes the attempted and successful total syntheses of these natural products and provides a summary of the strategies developed in the years since their isolation.1 Introduction2 Biosynthesis3 Early Studies4 Total Synthesis of Mycocyclosin5 Overview6 Wood’s Total Syntheses of Herqulines B and C7 Baran’s Total Syntheses of Herqulines B and C8 Schindler’s Total Syntheses of Herqulines B and C9 Conclusions
Keywords: total synthesis; herqulines; macrocycles; strain; Birch reduction